Health coach-supported mobile health intervention to improve adherence to lipid-lowering medications (AdLip): Design and rationale of a multicentre randomized controlled trial protocol - Qi Chwen Ong; Emina Obarcanin; Iva Bojic; Sock Hwee Tan; Sameera Senanayake; Sanjeewa Kularatna; Nicholas Graves; Siew Pang Chan; Jun Long Marvin Sim; Derek Hausenloy; Mark Yan Yee Chan; Andy Wai Hoong Khong; et al. (PLoS ONE, 2026)
Background Elevated low-density lipoprotein cholesterol is one of the major modifiable risk factors for cardiovascular disease. Lipid management is integral to primary and secondary prevention of cardiovascular disease, but undermined by high prevalence of non-adherence to lipid-lowering medications. Innovative, personalized multicomponent interventions may address the gaps in medication non-adherence. We aim to evaluate the effectiveness of a human coach-supported digital personal health assistant (mobile health app) intervention in improving adherence to statins in adults with hyperlipidaemia. Methods AdLip is a multicentre, open-label, parallel, two-arms, randomized controlled trial aiming to recruit a minimum of 376 adult participants who are non-adherent to statins from primary care ambulatory clinic setting in Singapore. Participants recruited will be randomly assigned (1:1) to human-coach supported mobile health app intervention or control group. The primary outcome will be adherence to statins at 6 months, measured by Medication Adherence Report Scale-5. Secondary outcomes will include change in serum low-density lipoprotein cholesterol levels, health motivation and attitudes, self-efficacy, self-care behaviours, quality of life, app acceptability, user engagement, and cost-effectiveness. Outcomes will be analysed using intention-to-treat approach. Discussion The AdLip trial will provide empirical evidence on a multicomponent approach to the long-standing challenge of suboptimal adherence to statins in a multi-ethnic Asian setting. Findings from this study may inform a more personalized approach to addressing non-adherence in the short term, and how it relates to cardiovascular disease prevention in the longer term. Trial Registration: ClinicalTrials.gov NCT06614049 .